2005
DOI: 10.1063/1.1927713
|View full text |Cite
|
Sign up to set email alerts
|

Radiation resistance of electro-optic polymer-based modulators

Abstract: Mach–Zehnder interferometric electro-optic polymer modulators composed of highly nonlinear phenyltetraene bridge-type chromophores within an amorphous polycarbonate host matrix were investigated for their resistance to gamma rays and 25.6 MeV protons. No device failures were observed and the majority of irradiated modulators exhibited decreases in half-wave voltage and optical insertion losses compared to nonirradiated control samples undergoing aging processes. Irradiated device responses were attributed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 14 publications
4
24
0
Order By: Relevance
“…In a 2003 investigation it was demonstrated that devices not strongly poled (therefore possessing large V values) were likely to de-pole when irradiated by gamma-rays 11 . In a subsequent investigation it was observed that some strongly poled devices actually experienced a substantial lowering of their V π values when irradiated by gamma-rays over a low dose range 8 . Figure 4 is the V π response of several Mach-Zehnder EO modulators comprised of a guest-chromophore (phenyltetrane)-and host-polymer (amorphous polycarbonate) irradiated by 60 Co gamma-rays at Sandia National Laboratory and irradiated by 25.6 MeV protons using the isochronous cyclotron located at Crocker Nuclear Laboratory (CNL) 8 .…”
Section: Radiation Effects In Polymer Eo Modulatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a 2003 investigation it was demonstrated that devices not strongly poled (therefore possessing large V values) were likely to de-pole when irradiated by gamma-rays 11 . In a subsequent investigation it was observed that some strongly poled devices actually experienced a substantial lowering of their V π values when irradiated by gamma-rays over a low dose range 8 . Figure 4 is the V π response of several Mach-Zehnder EO modulators comprised of a guest-chromophore (phenyltetrane)-and host-polymer (amorphous polycarbonate) irradiated by 60 Co gamma-rays at Sandia National Laboratory and irradiated by 25.6 MeV protons using the isochronous cyclotron located at Crocker Nuclear Laboratory (CNL) 8 .…”
Section: Radiation Effects In Polymer Eo Modulatorsmentioning
confidence: 99%
“…In a subsequent investigation it was observed that some strongly poled devices actually experienced a substantial lowering of their V π values when irradiated by gamma-rays over a low dose range 8 . Figure 4 is the V π response of several Mach-Zehnder EO modulators comprised of a guest-chromophore (phenyltetrane)-and host-polymer (amorphous polycarbonate) irradiated by 60 Co gamma-rays at Sandia National Laboratory and irradiated by 25.6 MeV protons using the isochronous cyclotron located at Crocker Nuclear Laboratory (CNL) 8 . Figure 4 shows that V π decreased following irradiation by gamma-rays and is only slightly altered by proton irradiations.…”
Section: Radiation Effects In Polymer Eo Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…While there have been various claims that many polymer materials used in fabricating PBPs are intrinsically resistant to ionizing radiation, verification to this extent has only been recently investigated [1][2][3][4][5][6][7][8][9][10][11][12]. Recent studies clearly indicate that to favorably and efficiently impact the development of cutting-edge organic/polymer based photonics technology for reliable operation in the space-radiation environment, acquisition of empirical irradiation data and a thorough analysis of the radiation induced effects are required at the earliest stages of component development.…”
Section: Introductionmentioning
confidence: 99%